Relative and absolute reliability of specific kickboxing circuit training protocol in male kickboxers - Ouergui, I.; Marzouki, H.; Houcine, N.; Franchini, E.; Gmada, N.; Bouhlel, E. (Science & Sports, 2016)
Objective: Kickboxing is a sport that elicits high metabolic and technical demands. The effectiveness of training methods in kickboxers has been assessed using different functional and activity outcome measures. The purpose of the current study was to investigate the relative and absolute reliability and the usefulness of a specific kickboxing circuit training protocol (SKCTP) in well-trained kickboxers. Methods: Twenty kickboxers participated in the study (mean ± SD): age: 21.3 ± 2.7 years, height: 170 ± 5.0 cm, body mass: 73.9 ± 13.9 kg. The athletes performed the SKCTP twice separated by 7 days. Hormones (cortisol, testosterone, growth hormone [GH]), blood lactate ([La]), blood glucose, were measured at rest and after circuit and delta (?) (the difference between rest and after circuit values) was determined. Heart rate (HR) and rating of perceived exertion (RPE) were recorded after each round (R) and the circuit was video-taped for subsequent technical analysis. Relative reliability was determined using an intraclass correlation coefficient (ICC), and absolute reliability with coefficient of variation (CV), standard error of measurement (SEM), and the minimal detectable change at the 95% confidence interval (MDC95). Results: Relative reliability (ICC) for hormonal, physiological parameters and RPE scores ranged from fair to good (0.4-0.8) except for [La] which was poor (ICC < 0.40). ICC was excellent for the technical performances (ICC > 0.90) indicating an excellent agreement from a relative perspective. Absolute reliability expressed as the coefficient of variation (CV) was low for delta lactate, glucose rest and after circuit, HR, RPE and technical performances (0.55-9.3%), while it was relatively high for lactate, GH, cortisol and testosterone (15.6-88.4%). SEM was also relatively high for these parameters. However, the SEM was low for glucose values (after circuit, 2.7%), for HR (3.7, 2.8, 2.3, after round 1, 2, and 3 respectively), and for RPE after round2 (4.8%) and 3 (3.6%). The mean bias ± 95% limits of agreement were acceptable for most of the hormonal and metabolic parameters selected. For kickboxing techniques, bias ± 95% limits of agreement were -2.3 ± 5.6 for punches, 0.9 ± 3.3 for kicks, -0.7 ± 2.4 for punches combinations, and 0.9 ± 3.3 for punches/kicks combinations. The smallest worthwhile changes (SWC) for the punches, kicks, punches combinations and punches/kicks combinations were 7, 3, 2 and 3 respectively, therefore exceeding the SEM and rating the SKCTP as "good". Conclusion: The SKCTP is reproducible in trained kickboxers. It can be used as a training tool that simulates combat kickboxing in terms of its metabolic and technical requirements.